Diabetes service decentralization to primary healthcare unit in Tigray, Ethiopia: A pilot study - Merhawit Atsbha Abera; Haregeweyni Gebreselassie Alemu; Hailemariam Berhe Kahsay; Abraha Hailu Weldegerima; Afework Mulugeta; Mengistu Hagazi Tequare; Afewerki Tesfahunegn Nigusse; Migbnesh Gebremedhin Weledegebriel; Tsega Cherkos Dawit; Ephrem Berhe; Tarekegn Geberhiwot (PLoS ONE, 2025)
Background The prevalence of diabetes mellitus has been increasing in the past few decades. Mortality and morbidity have increased faster in low- and middle-income countries than in high-income countries. In Ethiopia it has been a practice to handle most diabetes mellitus patients in general and referral hospitals which in turn caused over burden in these hospitals. Besides, the possibility of implementing diabetic care service in primary health care facilities is not assessed in Ethiopia. The aim of this study was to decentralize and implement diabetic service in primary health care facilities in Tigray. Methods and materials The study was conducted in Tigray region, at Hagereselam primary hospital from September 2019 to September 2020. A pilot study which aimed to bring diabetes services to non-specialized health care facilities. Diabetic patients who were on follow up in tertiary hospital (Ayder Comprehensive Specialized Hospital) were moved to Hagereseam primary hospital voluntarily, which is the main study site. The data were collected by trained health professionals and the data collection tool was adapted and developed from national guideline and analysed through SPSS 21. Independent t-test and chi-square was applied to compare the outcomes among study participant groups. Results The mean and median Fasting Blood Sugar (FBS) level was 171mg/dl and 151.5 (IQR = 109.5–180.7) respectively. and the mean difference of FBS with randomly selected patients in a referral hospital was 3.55 (p = 0.8) which shows no significant difference. Mean systolic BP and haemoglobin A1c were 114.2 mmHg and 8.34% respectively. Conclusion There is no significant difference in the diabetes service among the primary and tertiary hospital. Diabetes service can be decentralized to primary health care facilities without compromising the quality of diabetic care. Further large implementational study is necessary to overcome the problems in the decentralization of service delivery in diabetes service.